Cuantificación de antocianinas totales en el extracto acuoso de zea mays l variedad morado y determinación de la capacidad antioxidante in vitro - Bautista Portal, Sheylla Katherine (2010)
The field of phytotherapy and Traditional Medicine banks of genetic resources are very prominent in the world but little studied in our country. Zea mays L variety Purple (purple corn) was one of the main food of indigenous peoples which is attributed medicinal properties due to chemical compounds one of which is the known effect of antioxidant anthocyanins. This study aims to quantify anthocyanins in the aqueous extract of Zea mays L variety purple and determine the antioxidant capacity in vitro using the pH differential methods Brand - Williams respectively. Purple corn was collected from five locations of Peru Arequipa, Ayacucho, Ancash, Lima and Cuzco. First select the sample, then cut into small pieces then prepare an aqueous extract of the filtrate led to a concentration of 5%. For the concentration of anthocyanins 1 ml was taken and prepared for each of the prepared samples was carried absorbance readings in the spectrophotometer Jenway to 700nm and 510 nm with the data was calculated the concentration of anthocyanins expressed as mg / L, the ability antioxidant of the aqueous extract is diluted to a concentration of 100 mg / mL for each sample prepared was carried absorbance readings at 517nm Jenway spectrophotometer, with data from the antioxidant capacity was calculated. The concentration of anthocyanins and antioxidant capacity found in the aqueous extract of Zea mays L purple variety of the five regions has a significant difference to the place of origin